(untitled) (Bangladesh Journal of Medical Science, 2025)
Artificial Intelligence (AI) has revolutionized dental and medical diagnosis by leveraging machine learning (ML) and deep learning (DL) algorithms to analyze complex diagnostic data, enhance accuracy, and optimize patient care. AI applications, such as convolutional neural networks (CNNs) for dental radiographic analysis and tools like IBM Watson for Oncology in personalized treatment planning, have demonstrated diagnostic accuracies comparable to expert clinicians, reducing errors and improving early disease detection. Despite these advancements, challenges such as data privacy, algorithm transparency, and ethical concerns, including the potential dehumanization of care, limit widespread adoption. AI’s future in healthcare is promising, with advancements expected to facilitate early diagnosis, lower costs, and improve outcomes through real-time health monitoring and predictive analytics. Strategic collaborations, ethical vigilance, and global standards are essential to harness AI’s full potential in transforming healthcare. BJMS, Volume: 24. Supplementary Issue 2025, Page : 7-8